MOTORCYCLE SAFETY PARKING SYSTEM AT HOME WITH ARDUINO-BASED BLUETOOTH APPLICATION - Syamsudduha Syahrorini (Antis-Publisher, 2024)
The community feels that security at this time is not conducive, a lot of theft, robbery and robbery of motorbikes, and resulting in material losses for certain people is considered large. The increasing needs of the community in using safety devices on motorbikes, this has led to the creation of safety devices on motorbikes. This security system uses two microcontrollers that are interconnected by using Bluetooth. Bluetooth will detect a connection between the motorcycle and the house, this connection will continuously issue a signal and disconnected if the motorcycle and the house are not connected. Then the disconnection will be used as input data by the microcontroller and processed, so as to make the alarm sound and the electric motorcycle dies. Then there is a notification via SMS to the owner according to the time period that has been set in the program which is five seconds.